Ultra‐Stretchable and Fast Self‐Healing Ionic Hydrogel in Cryogenic Environments for Artificial Nerve Fiber (Adv. Mater. 16/2022). Issue 16 (21st April 2022) - Wang, Chan; Liu, Ying; Qu, Xuecheng; Shi, Bojing; Zheng, Qiang; Lin, Xubo; Chao, Shengyu; Wang, Changyong; Zhou, Jin; Sun, Yu; Mao, Gengsheng; Li, Zhou
Abstract : Artificial Nerve Fibers Artificial nerve fibers with self‐healing ability and stretchability in a cryogenic environment help construct fast and complex information interaction networks for bionic intelligent robots, as described by Zhou Li and co‐workers in article number 2105416 . Once accidental mechanical damage to the robot occurs, the artificial nerve fibers can autonomously recover their function and appearance in a short time. This is essential for robots to complete tasks in dynamic extreme environments.